2017
DOI: 10.1186/s13046-017-0545-x
|View full text |Cite
|
Sign up to set email alerts
|

ERβ1 inhibits metastasis of androgen receptor-positive triple-negative breast cancer by suppressing ZEB1

Abstract: BackgroundIncreasing evidence has indicated an important role for estrogen receptor beta 1 (ERβ1) in breast cancer. However, the role of ERβ1 in the metastasis of androgen receptor (AR)-positive triple-negative breast cancer (TNBC) and the underlying mechanisms are still unknown.MethodsStable ERβ1-expressing TNBC cell lines were generated for this study. We detected the abilities of cell migration and invasion by wound-healing and transwell assays and the expression of E-cadherin and N-cadherin by quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…In breast cancer, knockdown of ZEB1 can lead to the downregulation of inflammatory cytokines related to poor prognosis including IL6 and IL8 (Katsura et al, ). ERβ1 can repress androgen receptor‐positive triple‐negative breast cancer metastasis via targeting ZEB1 (Song et al, ). ZEB1 can promote ER‐α promoter hypermethylation and induces antiestrogen resistance in breast cancer (Zhang, Zhou, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, knockdown of ZEB1 can lead to the downregulation of inflammatory cytokines related to poor prognosis including IL6 and IL8 (Katsura et al, ). ERβ1 can repress androgen receptor‐positive triple‐negative breast cancer metastasis via targeting ZEB1 (Song et al, ). ZEB1 can promote ER‐α promoter hypermethylation and induces antiestrogen resistance in breast cancer (Zhang, Zhou, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA NEAT1 can play a vital role in nuclear paraspeckles and regulate RNA splicing and transcription (Naganuma & Hirose, 2013). NEAT1 can affect the development of mouse mammary gland (Standaert et al, 2014). NEAT1 can serve as an oncogenic lncRNA in several cancers, including breast cancer (Choudhry et al, 2015;Guo et al, 2015;Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, in MB-231 cells, DPN caused significant decrease in cellular invasion. This discrepancy could be due to the that fact that a recent study [ 67 ] had shown that MB-231 cells express androgen receptor (AR) and that in AR positive TNBC cells, ERβ decreases cellular invasion and migration. Another discrepancy could be due to the fact that these authors used an over-expressing ERβ construct, used FBS and phenol red containing media to determine invasion instead of using hormonal free FBS/phenol red free media.…”
Section: Discussionmentioning
confidence: 99%
“…ERβ1 and ERβ2 (also known as ERβcx) are the best characterized isoforms in breast tissue. 26 , 27 Although ERα has been well established as an important mediator of proliferation in breast cancer, the role of ERβ remains controversial. Hartman et al 28 found that ERβ-positive breast cancer had a higher histological grade than ERβ-negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%